Using basic research as a catalyst to exploit new technology-based innovations-a case study - Hameri, Ari-Pekka; Vuola, Olli.
The difficulties related to the commercialization, or even to the introduction, of new technologies and solutions to common problems are well documented. The paper presents a case on how to introduce new technology to a complex research environment, in order to catalyse its commercialization. The central theme of the approach is on understanding all the possible applications and implications that the new technology shares when implemented to replace conventional solutions. The potential customer of the new technology and the related technological domains must be mapped systematically to establish technological trajectories which overlap with the possible applications. This mapping provides the framework for detailed application analysis with pointers to the right people responsible for the potential application area.
The results produced indicate that three characteristic application classes for a new technology can be mapped. Special solutions pinpoint a non-standard application area where the new design is being implemented as a prototype. Research and development based applications require collaboration with the customer as the new technology may assist in achieving the goals set for the future. System applications emphasize the use of the new technology as part of a complete and widely used conventional system. A thorough case study is documented to demonstrate the classification of alternative application areas of a new technology. Also, the evolution of a new technology through different application classes is discussed. The case technology is related to high-speed electrical machines and the potential user is CERN, the European Laboratory for Particle Physics.
The case study is based on the problems encountered when attempting to commercialize and exploit new technology-based innovations. The study is related to high speed electrical machines in the European Laboratory for Particle Physics.
Keywords: Research; Technology-based innovations